Post-Coronary Artery Bypass Grafting Outcomes of Patients with/without Type-2 Diabetes Mellitus and Chronic Kidney Disease Treated with SGLT2 Inhibitor Dapagliflozin: A Single-Center Experience Analysis - Razan Al Namat; Letiția Doina Duceac; Liliana Chelaru; Marius Gabriel Dabija; Cristian Guțu; Constantin Marcu; Maria Valentina Popa; Florina Popa; Elena Roxana Bogdan Goroftei; Elena Țarcă (Diagnostics, 2023)
Introduction: Increasingly, SGLT2 inhibitors save patients with heart failure and comorbidities such as type-2 diabetes mellitus (T2DM) and chronic kidney disease (CKD); the inhibition of sodium-glucose cotransporter 2 (SGLT2) was first studied in patients with diabetes as a solution to lower glucose levels by preventing glucose reabsorption and facilitating its elimination; in the process, researchers took notice of how SGLT2 inhibitors also seemed to have beneficial cardiovascular effects in patients with both diabetes and cardiovascular disease. Aim: Our single-center prospective study assesses outcomes of post-coronary artery bypass grafting (CABG) rehabilitation and SLGT2 inhibition in CABG patients with/without T2DM and with/without CKD. Materials and Methods: One hundred twenty consecutive patients undergoing CABG were included in the analysis. Patients were divided into four subgroups: diabetes patients with chronic kidney disease (T2DM + CKD), diabetes patients without chronic kidney disease (T2DM−CKD), prediabetes patients with chronic kidney disease (PreD+CKD), and prediabetes patients without chronic kidney disease (PreD−CKD). Echocardiographic and laboratory investigations post-surgery (phase I) and 6 months later (phase II) included markers for cardiac ischemia, glycemic status, and renal function, and metabolic equivalents were investigated. Results: One hundred twenty patients participated, mostly men, overweight/obese, hypertensive, smokers; 65 had T2DM (18 with CKD), and 55 were prediabetic (17 with CKD). The mean ejection fraction increased by 8.43% overall but significantly more in the prediabetes group compared to the T2DM group (10.14% vs. 6.98%, p < 0.05). Overall, mean heart-type fatty-acid-binding protein (H-FABP) levels returned to normal levels, dropping from 68.40 ng/mL to 4.82 ng/mL (p = 0.000), and troponin data were more nuanced relative to an overall, strongly significant decrease of 44,458 ng/L (p = 0.000). Troponin levels in patients with CKD dropped more, both in the presence of T2DM (by 82,500 ng/L, p = 0.000) and in patients without T2DM (by 73,294 ng/L, p = 0.047). As expected, the overall glycated hemoglobin (HbA1c) levels improved significantly in those with prediabetes (from 6.54% to 5.55%, p = 0.000); on the other hand, the mean HbA1c changed from 7.06% to 6.06% (p = 0.000) in T2DM, and the presence or absence of CKD did not seem to make any difference: T2DM+CKD 7.01–6.08% (p = 0.000), T2DM−CKD 7.08–6.04% (p = 0.000), PreD+CKD 5.66–4.98% (p = 0.014), and PreD−CKD 6.03–4.94% (p = 0.00). Compared to an overall gain of 11.51, the GFRs of patients with CKD improved by 18.93 (68.15–87.07%, p = 0.000) in the presence of established diabetes and 14.89 (64.75–79.64%, p = 0.000) in the prediabetes group. Conclusions: Regarding the patients’ cardiac statuses, the results from our single-center analysis revealed a significant decrease in ischemic risk (H-FABP and hs-cTnI levels) with improvements in mean ejection fraction, glycemic status, and renal function in patients post-CABG with/without T2DM, with/without CKD, and with SGLT2 inhibitor dapagliflozin treatment while undergoing cardiac rehabilitation.